Modification of the Bio-Rad iQ-Check Listeria spp. Kit for the Detection of Listeria Species in Environmental Surfaces: AOAC Performance Tested MethodSM 090701. (29th January 2020) - Klass, Nicole; Bastin, Benjamin; Crowley, Erin; Agin, James; Clark, Mike; Tourniaire, Jean-Philippe; Pierre, Sophie; Quiring, Christophe; Chen, Yi; Ryser, Elliot; Salfinger, Yvonne
Abstract: Background: The Bio-Rad iQ-Check Listeria spp . Kit uses real-time PCR technology for detection of Listeria species in select food matrixes and environmental surfaces. Objective: The iQ-Check Listeria spp . method was modified to reduce the enrichment medium volume for environmental sponges from 225 and 100 to 60 mL and to reduce the enrichment time for sponges and swabs from 25 ± 1 to as short as 18 h. The modified method was validated with stainless steel, polystyrene plastic, and sealed concrete using sponges or swabs with two different neutralizing buffers (Letheen Broth and HiCap™ Neutralizing Broth). In addition, the Bio-Rad Free DNA Removal Solution was used for all environmental samples. Methods: The iQ-Check Listeria spp. modified method was compared with the reference culture method in the U.S. Department of Agriculture Food Safety and Inspection Service Microbiology Laboratory Guidebook Chapter 8.10 using an unpaired study design. Results: In the method comparison study, the iQ-Check Listeria spp. modified method demonstrated no statistical difference in performance between candidate and reference method results or between presumptive and confirmed results for all environmental surfaces analyzed using HiCap Neutralizing Broth (World Bioproducts LLC) and Letheen broth. Conclusions: The modified iQ-Check Listeria spp. method is an effective method for the detection of Listeria species in environmental surfaces using both types of neutralizing buffer. Highlights: The method modification was granted based on the data collected.